Carved arabesques with calligraphy, geometry and flora prevalent in the components of Malay Timber Houses - Kamarudin, Zumahiran (2010)
This paper presents the visual composition and significant attributes of arabesque designs applied in the carved components of Kelantan and Terengganu houses which are located in the northeastern region of Peninsular Malaysia. This study employed three methods of investigation: (1) analytical review on twelve sets of reports and measured drawings of seven houses in Kelantan and five houses in Terengganu which were obtained from KALAM, Universiti Teknologi Malaysia and the documents served as the main source of data, (2) interviews with five woodcarvers from Kelantan and Terengganu on art and crafts of woodcarving, types of motifs in the carved components and its attributes which serve as the inferential evidences, and (3) literatures on woodcarvings including its arts and craft-making and reviews on traditional Malay houses. The study found that several types of carved components like wall, door and window ventilation panels with distinctive application of flora, geometry and calligraphy as carving motifs were formed in two principal variants, namely monothematic and multi-thematic compositions. Carved arabesque with Arabic calligraphy and foliate patterns seemed omnipresent in houses belongs to religious patrons which were placed in certain orders within the fabrics of the houses. Indeed its characters as a dynamic art flourished on the incorporation of different ideas and yet embraced a strong Islamic identity. This study is useful in unveiling the significant meanings of the arabesque designs applied in Malay carvings which were considered as a manifestation of woodcarvers’ strong adherence to their artistic tradition anchored by Islamic belief.